Putusan Hatobangon Tentang Sanksi Ingkar Janji untuk Menikah Perspektif ‘Urf (Studi Kasus di Desa Pasar Simundol Kec. Dolok Sigompulon) - Siti Aisah Aritonang; Zainal Arifin Purba (LPPM Universitas Ekasakti Padang, 2023)
Hatobangon in the Mandailing region is called natoras, meaning the core figures in the community who are appointed by several people in each huta. Hatobangon acts as an advisor concerned with matters of Batak customary life. The focus of this research leads to how the hatobangon pattern in establishing the sanction of breaking a promise to marry as a new case and the review of Islamic law regarding the sanction. This research was conducted based on field research, data needed in the community environment and emphasized the results of data collection from informants. To understand this research, the author uses a conceptual approach, namely the concept of hatobangon in determining sanctions and their conformity with Islamic law, then examining the case (case approach). The sanction of denial of jani in a customary manner (custom) that applies in community life as long as it does not contradict the teachings and rules of Islam, then the custom is permissible. The position of customary law ('urf) according to the provisions of Islamic fiqh, is allowed which is shahih or al-'adah ashahihah, i.e. 'urf which does not contradict Islamic law. The problem of custom, in fiqh analysis is related to the concept of benefit (maslahah mursalah). Benefits that are common and may not yet apply, even things that will be enforced. Regarding al-a'dah ashahihah this gives rise to the rule of